Formação continuada de professores de línguas estrangeiras mediada pelo cinema : contribuições da teoria da atividade - Stefani, Viviane Cristina Garcia de (2015)
This study lines up with the goals of the National Project for Teacher Education, Critical Education, New Literacies and Multiliteracies which intend to contribute to Initial and Continuing Education of Foreign Language Teachers. Its goal is to deepen the discussion of theoretical and methodological issues of language under the light of the critical literacies, allowing participants to create critical-reflective attitudes toward the new proposals and their own practices in the classroom. Inserted in this research context, our study aims to analyze the impact of the use of the cinema as a pedagogical tool, in a continuing education course for foreign language teachers (English and Spanish) from public schools. We assume that teaching a foreign language through films motivates the learner, assists in the development of communication skills and stimulates the autonomous learning. In the period of the course (30 hours) we could offer theoretical support to help the teachers to analyze and prepare teaching activities with filmic content. Besides the theoretical assistance, we offer opportunities for interaction and exchange of experience among the participants, so all the prepared activities could be shared and analyzed by the group before being applied in the classroom. The data obtained through questionnaires, field notes and focal groups were analyzed based on the Activity Theory, recognizing that we are all a source of knowledge and we can act collaboratively to expand the construction of meaning. Thus, the protagonists of the research were responsible for each other's learning. Activity Theory is exemplified in three crucial moments of learning: 1) The goal we intent to reach is shown (in the case of this study, the goal was to teach foreign language using the film as a tool), giving a model, encouraging the teachers not to reproduce, but rather to be creative on this model; 2) We describe the instrument's acquisition process, with the constant comings and goings, frustrations and delights that are on the course to achieve the desired goal (time when teachers begin the process of elaboration of didactic activities); 3) the complexity of the task is described, which requires the ability to work in groups (moment of exchange of experiences between teachers about the results of development and implementation of activities). The results of the study indicate that the cinema is a motivating and efficient tool for teaching foreign languages, and the exchange of experiences and interaction fostered among teachers were important in solving problems, contributing effectively to their education, as well as to a significant foreign language teaching.